The following program demonstrates how to Compute the Sum of a Series in Java.

In this program, we have two input numbers: n1, and n2. While the number n2 indicates an option that takes a value of either 1 or 2.

When n2=1, the series sum will be computed as follows.

sum=n1-(n1-1)+(n1-2)-(n1-3)+(n1-4)…………..1

Similarly, for n2=2, we want to compute the sum as follows:

sum=n1+(n1-1)-(n1-2)+(n1-3)-(n1-4)…………1

The following code implements the above logic.

```
public class Sequences
{
public static void main(String[] args)
{
System.out.println(secondSequence(6, 1));
System.out.println(secondSequence(6, 2));
}
public static int secondSequence(int input1, int input2)
{
int ans=input1, n, t, x1=-1, x2=1;
n=input1;
if(input2==1)
{
for(int i=1;i<=n;i++)
{
t=n-i;
t=t*x1;
ans+=t;
x1=x1*(-1);
}
}
if(input2==2)
{
for(int i=1;i<=n;i++)
{
t=n-i;
t=t*x2;
ans+=t;
x2=x2*(-1);
}
}
return ans;
}
}
```

**Output**

**Further Reading**

Java Practice Exercise

Princites